A persona-based exploration of rabies post-exposure prophylaxis seeking behavior and its implication for communication strategic planning: Evidence from Thailand - Jitjayang Yamabhai; Patoo Cusripituck; Teerawan Mingbualuang; Nareerat Sangkachai; Wimwiga Sakchainanon; Chanatda Tungwongjulaniam; Onphirul Yurachai; Ratana Theerawat; Anuwat Wiratsudakul (One Health)
Rabies is a lethal zoonotic illness that claims over 59,000 lives annually. However, this fatality can be avoided by postexposure prophylaxis (PEP). This study aimed to identify and characterize different personas of individuals regarding their PEP-seeking behavior and develop tailored communication strategies to encourage PEP adoption among these distinct groups effectively. We categorized our subjects, residing in two districts of Chonburi province, Thailand, into three groups: (i) individuals with a history of dog bites who underwent PEP; (ii) individuals bitten by dogs who did not receive PEP; and (iii) individuals who had never been bitten. Subsequently, we employed an empathy map, a visual method, and a customer journey map to better understand the participants' experiences and perceptions. A total of 38 individuals were interviewed. We categorized the participants into three distinct personas: positive, neutral, and negative trends. Individuals classified within the positive trend strongly advocate for seeking rabies vaccines in the event of a dog bite. Meanwhile, individuals who have a neutral inclination are more likely to contemplate getting vaccinated following a dog bite, particularly if the injury is substantial. Those with a negative trend demonstrate a notable lack of attention or concern toward preventing rabies. A lack of attention to the potential severity of the issue characterizes their attitude. Notably, nearly half (44.74 %; 17/38) of the individuals involved in the study indicated utilizing interpersonal communication, followed by digital platforms (42.11 %; 16/38) and traditional communication channels (10.52 %; 5/38). Tailoring communication modalities to suit each specific group is crucial for effective outreach.